PENGARUH STORE’S ATMOSPHERE DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN NICK COFFEE - Ade Tiara Yulinda; Erwin Febriansyah; Fenti Sukma Riani (UNIVED Press, 2021)
This study aims to determine the effect of store's atmosphere and product quality on purchasing decisions Nick Coffee Consumers in Bengkulu City. This research is a quantitative study with a sample of 100 respondents, using accidental sampling technique . Data collection techniques using observation and questionnaires. Data analysis techniques using classical assumption test, multiple linear regression, coefficient of determination (R2) and hypothesis testing. The results of this study can be seen from the multiple linear regression test with calculations are performed using SPSS, the comparison between the (n-k-1) = 100-2-1 = 97 (1.9826).) . From the results of hypothesis testing that Store's Atmosphere (X1) has a positive effect on purchasing decisions on Nick Coffee consumers in Bengkulu City , with T test results showing a significance value of 0,000 <0.050 and Product Quality (X2) has a positive effect on purchasing decisions on Nick Coffee City consumers Bengkulu , with the T test results showing a significance value of 0,000 <0.050 . Testing the hypothesis of the T test and F test shows that the Store's Atmosphere and Product Quality have a significant effect on purchasing decisions with a significance level <0.05. This means that Ho was refused Ha was accepted. In other words Store's Atmosphere and Product Quality have a significant effect both partially and jointly on purchasing decisions at Nick Coffee Bengkulu City . This is evidenced by the f test showing a significance value of 0.000 <0.05.